(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article analyzes the interpretation of the episodic image of Beruni in the novel by Maksud Koriev “Ibn Sino”. Despite the fact that the image of Beruni in the novel is episodic, the author managed to reveal, within the limits of the novel’s capabilities, his characteristic features as a historical personality and a great scientist.